2017
DOI: 10.1104/pp.16.01243
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule-Associated Protein MAP18 Affects ROP2 GTPase Activity during Root Hair Growth

Abstract: Establishment and maintenance of the polar site are important for root hair tip growth. We previously reported that Arabidopsis (Arabidopsis thaliana) MICROTUBULE-ASSOCIATED PROTEIN18 (MAP18) functions in controlling the direction of pollen tube growth and root hair elongation. Additionally, the Rop GTPase ROP2 was reported as a positive regulator of both root hair initiation and tip growth in Arabidopsis. Both loss of function of ROP2 and knockdown of MAP18 lead to a decrease in root hair length, whereas over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 75 publications
0
53
0
Order By: Relevance
“…Kang et al (2017) found that MAP18 and ROP2 are in the same genetic pathway and that they interact physically with MAP18, preferentially binding the inactive form of ROP2 and thereby promoting ROP2 activity. Kang et al (2017) went on to show that MAP18 competes with the ROP2 guanine dissociation inhibitor for binding to ROP2. From these and earlier studies (Wang et al, 2007;Zhu et al, 2013), Kang et al (2017) suggest that MAP18 functions through ROP2 to reinforce polarity and independently of ROP2 by modulating the cytoskeleton.…”
Section: Microtubule Cytoskeletonmentioning
confidence: 99%
See 3 more Smart Citations
“…Kang et al (2017) found that MAP18 and ROP2 are in the same genetic pathway and that they interact physically with MAP18, preferentially binding the inactive form of ROP2 and thereby promoting ROP2 activity. Kang et al (2017) went on to show that MAP18 competes with the ROP2 guanine dissociation inhibitor for binding to ROP2. From these and earlier studies (Wang et al, 2007;Zhu et al, 2013), Kang et al (2017) suggest that MAP18 functions through ROP2 to reinforce polarity and independently of ROP2 by modulating the cytoskeleton.…”
Section: Microtubule Cytoskeletonmentioning
confidence: 99%
“…To investigate MAP18's function in root hairs, Kang et al (2017) tested for genetic and physical interactions between MAP18 and Rho/Rac of Plants2 (ROP2), a small GTPase considered to be a master regulator of tip growth in root hairs (Jones et al, 2002). Kang et al (2017) found that MAP18 and ROP2 are in the same genetic pathway and that they interact physically with MAP18, preferentially binding the inactive form of ROP2 and thereby promoting ROP2 activity. Kang et al (2017) went on to show that MAP18 competes with the ROP2 guanine dissociation inhibitor for binding to ROP2.…”
Section: Microtubule Cytoskeletonmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, RHs developed in pluripetala (plp) mutant plants, which lack protein prenylation, suggesting that type II ROPs possibly also contribute to RH initiation (Running et al, 2004;Sorek et al, 2011;Chai et al, 2016). ROP2 activity also is regulated by Microtubule Associated Protein18, which interacts preferentially with GDP-bound ROP2 and competes with RhoGDI (Kang et al, 2017).…”
Section: Regulation Of Rh Tip Growthmentioning
confidence: 99%